2015
DOI: 10.5597/lajam00195
|View full text |Cite
|
Sign up to set email alerts
|

Detection of infection with Leptospira spp. in manatees (Trichechus inunguis) of the Peruvian Amazon

Abstract: The Amazonian manatee (Trichechus inunguis) is an aquatic mammal (Family Trichechidae) that inhabits freshwater environments. It is endemic to the Amazon Basin, and occurs from Marajó Island (at the mouth of the Amazon River in Brazil) to the headwaters of the floodplain in Colombia, Peru and Ecuador. Little is known of the causes of death or the prevalence of zoonotic organisms in manatees from Peru; however, Leptospira spp. have been reported to cause mortalities in marine mammals. Here we evaluated the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Previous studies reported the prevalence of leptospirosis or seropositivity to Leptospira spp. in the sirenian Peruvian Amazon manatees ( Trichechus inunguis ) [18] as well as in pinnipeds including harbor seals ( Phoca vitulina ) [19, 20], Northern elephant seals ( Mirounga angustirostris ) [21], California sea lions ( Zalophus californianus ) [2226, 17], and Chilean South American sea lions ( Otaria byronia ) [27]. Most recently, two serovars – Pomona and Calicola – of Leptospira interrogans were detected in serum samples of endangered Caspian seals ( Pusa caspica ) in the Caspian Sea off Northern Iran [28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the prevalence of leptospirosis or seropositivity to Leptospira spp. in the sirenian Peruvian Amazon manatees ( Trichechus inunguis ) [18] as well as in pinnipeds including harbor seals ( Phoca vitulina ) [19, 20], Northern elephant seals ( Mirounga angustirostris ) [21], California sea lions ( Zalophus californianus ) [2226, 17], and Chilean South American sea lions ( Otaria byronia ) [27]. Most recently, two serovars – Pomona and Calicola – of Leptospira interrogans were detected in serum samples of endangered Caspian seals ( Pusa caspica ) in the Caspian Sea off Northern Iran [28].…”
Section: Introductionmentioning
confidence: 99%
“…Although the MAT has been used extensively in many terrestrial and marine species, it has not been validated in these species and does not determine the presence or absence of disease. Given previous reports of low titers (1:25 and 1:32) in both subspecies of the West Indian manatee (Bossart et al 2012, Smith et al 2016) and in the Amazonian manatee (Delgado et al 2013), it is possible that our study titers were below the detection limit of 1:32. The high seroprevalence in Amazonian manatees often without signs of clinical disease suggests that T. gondii infections in immunocompetent manatees are likely subclinical (Delgado et al 2013).…”
Section: Florida and Antillean Manateesmentioning
confidence: 76%
“…Given previous reports of low titers (1:25 and 1:32) in both subspecies of the West Indian manatee (Bossart et al 2012, Smith et al 2016) and in the Amazonian manatee (Delgado et al 2013), it is possible that our study titers were below the detection limit of 1:32. The high seroprevalence in Amazonian manatees often without signs of clinical disease suggests that T. gondii infections in immunocompetent manatees are likely subclinical (Delgado et al 2013). T. gondii infection in the Antillean and Florida manatee populations is probably rare and suggests a low risk of parasite infection to sirenians.…”
Section: Florida and Antillean Manateesmentioning
confidence: 76%
“…The other isolation of serovar Pomona was obtained from the kidney of a common bottlenose dolphin ( Tursiops truncates ) collected in Sardinia (Italy) [ 80 ]. These are the only isolations from whale and dolphin species, among several investigated species around the world [ 40 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Leptospira Isolation On “Unconventionamentioning
confidence: 99%